A survey on the importance of topics for pharmacoinformatics course for Bachelor and Master pharmacy degrees / Imas Nur Amelia Zainal - Zainal, Imas Nur Amelia (2015)
This study was aimed to identify and review literature that presented information about development and application of pharmacoinformatics in pharmaceutical and health sciences. Besides that, this study also assessed the level of importance of the suggested topics for pharmacoinformatics course for Bachelor and Master of pharmacy degrees. Methods. For the review, the quality assessment tool for quantitative studies suggested by Cochrane Collaboration was adopted. Independent assessment was conducted to evaluate the quality of the included studies. A databases used for this study and review was PubMed and Science Direct. Both databases search was conducted using the English key words, "pharmacoinformatics", "pharmacy informatics", "medical informatics", "health informatics" and etc. For the survey study, a quantitative cross sectional study using questionnaire was distributed online via email invitation as well using printed questionnaires. This cross-sectional survey was performed from December 2013 to May 2014 among pharmacy lecturers in both public and private universities and registered pharmacists in ministry of health in the central part of Malaysia. The data were analyzed descriptively using Statistical Package for the Social Sciences (SPSS), version 20.0. The relative importance of the topics of Pharmacoinformatics course were quantified by the relative index method. Key findings. The search strategy resulted in the inclusion of sources, the majority of which expert opinion and examines the pharmacoinformatics relevance from a theoretical point of view (PubMed, n = 72). Based from the keyword of "informatics" and "pharmacy" on PubMed databases using advanced search, 59 articles was obtained with particular fields which is title and abstract. The articles are then being filtered by article type, publication dates and languages of articles